2021
DOI: 10.1248/bpb.b21-00288
|View full text |Cite
|
Sign up to set email alerts
|

Panaxytriol Inhibits Lipopolysaccharide-Induced Microglia Activation in Brain Inflammation <i>in Vivo</i>

Abstract: Brain inflammation is a pathological characteristic of neurodegenerative diseases. In this condition, excessively activated microglia elevate proinflammatory mediator levels. We previously reported that panaxytriol inhibited lipopolysaccharide (LPS)-induced microglia activation in vitro. However, the effects of panaxytriol on microglia activation in vivo require confirmation. In the present study, we found that panaxytriol suppressed both microglia and astrocyte activation by injected LPS intracerebrally to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Autopsy studies on human samples and investigations into animal models of slow-progressing illnesses have revealed a simultaneous occurrence of neuronal loss and heightened activated microglia within brain regions affected by lesions . Hiramatsu et al showed that panaxytriol suppressed both microglia activation by injecting LPS intracerebrally into mice with LPS-induced brain inflammation . Wang et al showed that Salidroside exerts neuroprotection by inhibiting microglia activation to repair spinal cord injury .…”
Section: Resultsmentioning
confidence: 99%
“…Autopsy studies on human samples and investigations into animal models of slow-progressing illnesses have revealed a simultaneous occurrence of neuronal loss and heightened activated microglia within brain regions affected by lesions . Hiramatsu et al showed that panaxytriol suppressed both microglia activation by injecting LPS intracerebrally into mice with LPS-induced brain inflammation . Wang et al showed that Salidroside exerts neuroprotection by inhibiting microglia activation to repair spinal cord injury .…”
Section: Resultsmentioning
confidence: 99%
“…Mice were anesthetized with intraperitoneal injection of a mixture of three anesthetic agents: 0.75 mg/kg medetomidine hydrochloride (Domitor, Nippon Zenyaku Kogyo, Koriyama, Japan), 4.0 mg/kg midazolam (Midazolam (SANDOZ), Sandoz K.K., Tokyo, Japan), and 5.0 mg/kg butorphanol tartrate (Betorphal, Meiji Seika Pharma, Tokyo, Japan) and perfused transcardially with 10 mL phosphate-buffered saline (PBS) at pH 7.4, followed by 10 mL of 4% paraformaldehyde ( Hiramatsu et al, 2021 ). The spinal cord (cervical1-5) was removed, immersed in the same fixative overnight, and then immersed in 25% sucrose in PBS for 48 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue preparation was completed as previously described [ 71 ] with minor modifications. Mice were anesthetized with a mixture of three anesthetic agents: 0.75 mg/kg medetomidine hydrochloride (Nippon Zenyaku Kogyo, Koriyama, Japan), 4.0 mg/kg midazolam (Sandoz K.K., Tokyo, Japan), and 5.0 mg/kg butorphanol tartrate (Meiji Seika Pharma, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%